APPLICATION OF THE CONCEPT OF KALA IN RELIGIOUS LIFE IN BANGLI SOCIETY - Dharma, I Wayan Yudhasatya (UHN I Gusti Bagus Sugriwa Denpasar, 2024)
Time is the most valuable thing to have and at the same time it is also the easiest thing to waste. So on this occasion the author determined this research with the title